Suplementasi tepung spirulina yang difermentasi untuk pertumbuhan dan tingkat kecerahan warna ikan mas koki (Carassius auratus L.) - Palinggi, Januarti; Mudeng, Joppy D.; Ngangi, Edwin L. A.; Kreckhoff, Reni L.; Mingkid, Winda M.; Mokolensang, Jeffrie F.; Tumembouw, Sipriana S. (e-Journal BUDIDAYA PERAIRAN, 2026)
Goldfish (Carassius auratus L.) is a freshwater ornamental fish commodity whose economic value is largely determined by its body color quality. This study aimed to evaluate the effect of fermented Spirulina sp. powder supplementation on the growth performance and color brightness of goldfish. The research used a completely randomized design (CRD) with four treatments (A: 0%, B: 3%, C: 6%, and D: 9% fermented spirulina) and three replications. Microalgae fermentation was carried out using baker's yeast (Saccharomyces cerevisiae) for 48 hours to increase nutrient bioavailability. The results showed that the highest absolute growth was obtained in treatment D (3.43 g), but statistically, there was no significant difference (P>0.05) across all treatments. The feed conversion ratio (FCR) showed the best efficiency at the 9% dose (0.66). For the color parameter, the best consistent brightness increase was produced by treatment B (3% dose). In conclusion, 3-6% fermented spirulina supplementation is recommended to maintain the balance between somatic growth and color pigment quality in goldfish. Keywords: Carotenoids, bioavailability, baker's yeast, feed nutrition.